(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Colorectal cancer is a formidable health problem worldwide. In men, it's the third most prevalent cancer, while in women; it's the second most common. Colorectal cancer occurrence has been on rise in patients younger than age 50, often referred to as early-onset disease. The main aim of the present work was to provide an overview of medicinal plants effective on colon cancer with respect to risk factors and prevention. The surge in colorectal cancer incidence in young adults is particularly alarming as the overall colorectal cancer frequency has been decreasing. Colorectal cancer, year by year, shows an increasing tendency in terms of both morbidity and deaths. Many factors may be responsible for the development of this disease, including genetic as well as environmental and lifestyle-related major risk factors like lack of physical activity, obesity, alcohol intake and smoking. Lifestyle factors are significant because of the potential for improving our understanding of the disease. Physical inactivity, obesity, smoking and alcohol consumption can also be addressed through therapeutic interventions. Treatment of young adults with colorectal cancer represents an unmet clinical need, especially as late diagnosis in this population might lead to the greatest loss of years of life. In this context, herbal plants like Allium sativum has a relevant role, and Sophoridine has found to have potential anti-colorectal carcinoma effect when tested on mice with tumorxenograft of SW480 cells subcutaneously in the mice armpit. Recent research indicates that grape, soybean, green tea, garlic, and pomegranate are the most effective plants against colon cancer.